Endoscopic TriModal imaging and biomarkers for neoplasia conjoined: a feasibility study in Barrett's esophagus. Issue 5 (15th October 2012) - Boerwinkel, D. F.; Di Pietro, M.; Liu, X.; Shariff, M. K.; Lao‐Sirieix, P.; Walker, C. E.; Visser, M.; O' Donovan, M.; Kaye, P.; Bergman, J. J. G. H. M.; Fitzgerald, R C.
Summary In Barrett's esophagus (BE), the normal squamous lining of the esophagus is replaced by specialized columnar epithelium. Endoscopic surveillance with autofluorescence imaging (AFI) and molecular biomarkers have been studied separately to detect early neoplasia (EN) in BE. The combination of advanced‐imaging modalities and biomarkers has not been investigated; AFI may help detecting biomarkers as a risk‐stratification tool. We retrospectively evaluated a cohort of patients undergoing endoscopy for EN in BE with AFI and correlated five biomarkers (HPP1, RUNX3, p16, cyclin A, and p53) in tissue samples with AFI and dysplasia status. Fifty‐eight samples from a previous prospective study were selected: 15 true‐positive (TP: AFI‐positive, EN), 21 false‐positive (FP: AFI‐positive, no EN), 12 true‐negative (TN1; AFI‐negative, no EN in sample), 10 true‐negative (TN2: AFI‐negative, no EN in esophagus). Methylation‐specific RT‐PCR was performed for HPP1, RUNX3, p16, and immunohistochemistry for cyclin A, p53. P < 0.05 was considered statistically significant. Bonferroni correction was used for multiple comparisons. P16, cyclin A, p53 correlated with dysplasia (P < 0.01, P = 0.003, P < 0.001, respectively). Increased p16 methylation was observed between TP versus TN2 (P = 0.003) and TN1 versus TN2 (P = 0.04) subgroups, suggesting a field defect. Only p53 correlated with AFI‐status (P = 0.003). After exclusion of EN samples, significance was lost. Although correlation with dysplasia status was confirmed for p16, cyclin A and p53, underlining the importance of these biomarkers as an early event in neoplastic progression, none of the investigated biomarkers correlated with AFI status. A larger prospective study is needed to assess the combination of AFI and a larger panel of biomarkers to improve risk stratification in BE.